The influence of ion implantation by phosphorous on structural changes in porous silicon - Swiatek, Z.; Lytvynchuk, I.; Fodchuk, I. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2004)
Structural changes in the surface layer of technologically treated silicon by ion implantation, chemical etching, and their combined action have been investigated by the X-ray diffractometry methods. The functional and quantitative differences in the thickness dependences of strains, values of maximum strain, level of lattice disturbance and extension of elastic strains nave been revealed after different steps of treatment. The essential modification of photoluminescence spectra was observed in the porous layer after implantation by phosphorus ions in the process of natural aging.